2016
DOI: 10.18488/journal.94/2016.2.1/94.1.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Weather Conditions on Solar Energy in Rivers State University of Science and Technology, Port Harcourt, Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Xiaoyuan et al showed in their work [20] that aerosol pollution in China reduces the production on optimally tilted fixed PV panels by up to 1.5 kWh/m 2 per day, incurring a high percentage decrease (25-35%) in polluted northern and eastern China. Etim et al in [21] showed also that solar energy decreases as relative humidity and high rainfall increase.…”
Section: Criteria For Choosing a Location For Solar Systemmentioning
confidence: 97%
“…Xiaoyuan et al showed in their work [20] that aerosol pollution in China reduces the production on optimally tilted fixed PV panels by up to 1.5 kWh/m 2 per day, incurring a high percentage decrease (25-35%) in polluted northern and eastern China. Etim et al in [21] showed also that solar energy decreases as relative humidity and high rainfall increase.…”
Section: Criteria For Choosing a Location For Solar Systemmentioning
confidence: 97%
“…Solar radiation prediction using empirical methods (Mubiru 2006) demonstrates direct and indirect influence of geographical and weather conditions (Yazdani et al 2016, Mubiru andBanda 2008). Rivington et al (2005) and Uko et al (2016) also reported the interdependence using sunshine duration. In Brunei Darussalam and Jaipur, India GHI is seen to depend linearly on atmospheric temperature and relative humidity (Yazdani et al 2016, Mukherji et al 2020).…”
Section: Introductionmentioning
confidence: 97%